Browser-based simulation for novice-friendly classroom robotics - Stein, Gordon; Jean, Devin; Brady, Corey; Lédeczi, Ákos (Frontiers in Computer Science, 2023)
Robots are a popular and engaging educational tool for teaching computational thinking, but they often have significant costs and limitations for classroom use. Switching to a simulated environment can eliminate many of these difficulties. By also providing students with a block-based programming environment, the barrier to entry can be further reduced. This paper presents a networked virtual robotics platform designed to create an environment which is highly accessible for novice students and their teachers alike, along with components of a curriculum designed to teach computational thinking skills through robotics programming challenges, including autonomous challenges and in-class competitions. Students access this platform through an extension of the same web interface used for programming their robots, which allows students to collaborate on code and view a shared simulated virtual space. Previously, this virtual robotics platform was used only to facilitate distance education. This paper demonstrates its use in an in-person class during the Spring 2022 semester, illustrating the affordances of a virtual robotics environment for face-to-face learning contexts as well. Students' computational thinking skills were evaluated with assessments both before and after the class, along with surveys and interviews given to determine their opinions and outlooks regarding computer science. The results show that students had a significant improvement in both attitudes and aptitudes.